Transvaginal and transrectal ultrasonographic comparison of follicular dynamics in successive waves of llamas (Lama glama) - Perez G., Uri (2021)
The ovarian follicular dynamics monitored by transrectal (TR) and transvaginal (TV) routes in successive waves was studied in 10 llamas older than 4 years, multiparous, without calves at foot, body condition of 3.0, during a period of 90 days in the reproductive season. The Sonostar SS8® ultrasound equipment was used with a linear transducer for transrectal examination and endocavitary microconvex transducer for transvaginal examination, both with a frequency of 6.5 MHz. The inter-wave interval was 20 ± 4.4 and 22.5 ± 5.3 via TR and VT, respectively; the number of follicles per cohort was 5.21 ± 0.92 and 6.38 ± 1.26 for TR and TV, respectively (p=0.0011); the maximum diameter of follicles was 12.49 ± 3.57 mm for TR and 13.56 ± 3.91 mm for TV; the growth rate was 0.70 ± 0.35 and 0.67 ± 0.32 mm/day for TR and TV, respectively. The regression equation for the ratio of the maximum follicular diameter and duration of follicular wave via TR was y=0.89766x+6.5554 (R²=0.423) and for the TV route y=0.8466x+10.184 (R²=0.479). The duration of the follicular phases was similar between both techniques except for the dominance phase (10.2±3.19 days for TR and 8.67±2.46 for TV, p=0.0418). The relationship between the follicular diameter and the number of follicles detected showed a low negative correlation (R²=-0.0827 for TV and R²=-0.0876 for TR). In conclusion, the transvaginal endocavitary transducer makes it possible to determine with greater precision the characteristics of llama follicular dynamics in their recruitment, dominance and regression phases with overlapping of follicular waves as an important characteristic.